RISK FACTORS FOR ACUTE NASOPHARYNGITIS IN THE WORK AREA OF THE PUSKESMAS (PUBLIC HEALTH CENTER) TOLANGOHULA - Lintje Boekoesoe; Ilyas Puluhulawa (International Journal of Health Science & Medical Research, 2023)
Acute nasopharyngitis, coughs, and colds or colds are the most common people suffer from. Runny nose/runny nose (rhinorrhoea), blocked nose, sore throat and headache, mild fever, muscle aches, and body weakness (fatigue). The novelty of this study is that it examines the risk factors for acute nasopharyngitis. The research aims to determine whether there is an influence of risk factors for acute nasopharyngitis in the work area of the Tolangohula Health Center. The type of research used is quantitative research, cross-sectional design, using a sampling technique, namely purposive sampling. The sample obtained during the investigation was 150. Data analysis used the Odds Ratio (OR) test. The results of the study from 150 respondents had good knowledge, namely 87 respondents (58%) with the incidence of acute nasopharyngitis for the non-nasopharyngitis category, namely 7 respondents (8.0%) while in the smoking category for nasopharyngitis, namely 55 respondents (87.3%) and in-home environment that did not meet the requirements, namely 84 respondents (55.3%) with the incidence of acute nasopharyngitis for the non-nasopharyngitis category, namely 17 respondents (20.2%) and for the nasopharyngitis category, namely 67 respondents (79.8%). The conclusion is that there is a relationship between knowledge and the incidence of acute nasopharyngitis, with the obtained p-value = 0.000, where the OR value = 43.956. There is a relationship between smoking habits and the incidence of acute nasopharyngitis, p = 0.000, where OR = 8.865, and there is a relationship between the home environment and the incidence of acute nasopharyngitis, p = 0.000, where OR = 0.165.